Natural deep eutectic solvents (NaDES): green solvents for pharmaceutical applications and beyond - Chevé-Kools, Emma; Choi, Young Hae; Roullier, Catherine; Ruprich-Robert, Gwenaël; Grougnet, Raphaël; Chapeland-Leclerc, Florence; Hollmann, Frank (Green chemistry : an international journal and green chemistry resource : GC, 2025)
Composed of various biosourced metabolites, NaDES offer significant economic, health, and environmental benefits. Their remarkable ability to interact with target compounds through non-covalent bonds enhances their versatility. As solvents, excipients, cofactors, catalysts, solubilisation promoters, stabilisers, and absorption agents, NaDES provide distinct advantages over conventional substances and can even act as active compounds themselves. Furthermore, their role in advancing innovative synthesis and formulation strategies, particularly in nanotechnology and biotechnology, is driving research in these areas. This review is the first to explore all the potential applications of NaDES in the pharmaceutical industry, while taking a comprehensive look at the theory behind them. It gives a precise definition of NaDES and describes their composition, characteristics, molecular interactions, preparation, stability and recovery. It presents detailed applications in pharmaceutical synthesis, extraction and formulation, and discusses roles as active compounds or tools for innovation. Using green metrics, the efficiency of routes including NaDES is compared to that of conventional processes. Lastly, this review addresses often overlooked points such as toxicity and process limitations.